Probing defects and electronic structure of Eu doped t-Mg2B2O5 nanocrystals using X-ray absorption near edge spectroscopy and luminescence techniques - Kumar, Jitender; Sharma, Aditya; Won, Sung Ok; Kumar, Ravi; Chae, Keun Hwa; Kumar, Shalendra; Vij, Ankush (PERGAMON-ELSEVIER SCIENCE LTD, 2020)
We report here the defects and electronic structure study of Eu (1%,3%,5%) doped t-Mg2B2O5 nanocrystals synthesized using low temperature combustion method, and probed using x-ray diffraction (XRD), transmission electron microscopy (TEM), X-ray absorption near edge spectra (XANES), photoluminescence (PL) and thermoluminescence (TL). The XRD analysis of all samples shows single phase triclinic crystal structure and average crystallite size decreases with Eu doping in Mg2B2O5. The experimental XANES spectra of each sample acquired at Eu M-5,M-4-edges were compared with simulated absorption edges using atomic-multiplet calculations, which clearly shows the presence of Eu3+ in Mg2B2O5. The O K-edge spectra of Eu doped Mg2B2O5 predicts the formation of O and Mg defects upon increasing Eu concentrations. The photoluminescence of Mg2-xEuxB2O5 nanocrystals at an excitation of 325 nm comprises of a group of sharp peaks owing to intra-4f transitions in Eu3+ and confirms the lowering of local symmetry with Eu concentration in Mg2B2O5. The effect of Eu doping on the trapping states was probed using TL after irradiating Mg2B2O5 with ultra-violet radiations (365 nm), which shows the presence of shallow and deep level trapping states. The corresponding activation energies of trapping states were determined using glow curve deconvolution method based on Kitti's general order equation.
Keywords: RARE-EARTH IONS; MAGNETIC-PROPERTIES; OPTICAL-PROPERTIES; SOLID-SOLUTIONS; PHOTOLUMINESCENCE; THERMOLUMINESCENCE; DEPENDENCE; MECHANISM; CRYSTAL; XANES